Influence of county-level geographic/ancestral origin on glioma incidence and outcomes in US Hispanics. Issue 2 (22nd July 2022) - Walsh, Kyle M; Neff, Corey; Bondy, Melissa L; Kruchko, Carol; Huse, Jason T; Amos, Christopher I; Barnholtz-Sloan, Jill S; Ostrom, Quinn T
Abstract: Background: Glioma incidence is 25% lower in Hispanics than White non-Hispanics. The US Hispanic population is diverse, and registry-based analyses may mask incidence differences associated with geographic/ancestral origins. Methods: County-level glioma incidence data in Hispanics were retrieved from the Central Brain Tumor Registry of the United States. American Community Survey data were used to determine the county-level proportion of the Hispanic population of Mexican/Central American and Caribbean origins. Age-adjusted incidence rate ratios and incidence rate ratios (IRRs) quantified the glioma incidence differences across groups. State-level estimates of admixture in Hispanics were obtained from published 23andMe data. Results: Compared to predominantly Caribbean-origin counties, predominantly Mexican/Central American-origin counties had lower age-adjusted risks of glioma (IRR = 0.83; P < 0.0001), glioblastoma (IRR = 0.86; P < 0.0001), diffuse/anaplastic astrocytoma (IRR = 0.78; P < 0.0001), oligodendroglioma (IRR = 0.82; P < 0.0001), ependymoma (IRR = 0.88; P = 0.012), and pilocytic astrocytoma (IRR = 0.76; P < 0.0001). Associations were consistent in children and adults and using more granular geographic regions. Despite having lower glioma incidence, Hispanic glioblastoma patients from predominantly Mexican/Central American-origin counties had poorer survival than Hispanics living in predominantly Caribbean-origin counties. Incidence and survival differences could be partially explained by state-level estimates of European admixture in Hispanics with European admixture associated with higher incidence and improved survival. Conclusions: Glioma incidence and outcomes differ in association with the geographic origins of Hispanic communities, with counties of predominantly Mexican/Central American origin at significantly reduced risk and those of Caribbean origin at comparatively greater risk. Although typically classified as a single ethnic group, appreciating the cultural, socioeconomic, and genetic diversity of Hispanics can advance cancer disparities research.